Differential Effects of Calcineurin and Mammalian Target of Rapamycin Inhibitors on Alloreactive Th1, Th17, and Regulatory T Cells. Issue 9 (September 2015) - Gallon, Lorenzo; Traitanon, Opas; Yu, Yuming; Shi, Bo; Leventhal, Joseph R.; Miller, Joshua; Mas, Valeria; L, Xu; Mathew, James M.
<x xml:space="preserve">Abstract</x> Background Previously, we had reported the role of tacrolimus (TAC) versus sirolimus (SRL) on the generation of regulatory T cells (Tregs) in primary MLR assays with SRL, demonstrating a uniquely supportive effect. However, the mechanisms associated with their actions on alloreactive human T cells are not fully understood. Therefore, we tested whether TAC and SRL differentially affect already alloactivated human CD4+ T-cell subsets. Methods Alloreactive CD4+CD45RA−/CD45RO+ T cells generated in 9-day MLR were cocultured with anti-CD3 and autologous antigen presenting cells plus interleukin (IL)-2 in presence of TAC, SRL, or both, and the Tregs generated after another 5 to 6 days were phenotypically, molecularly, and functionally characterized. Results Tacrolimus significantly and SRL modestly inhibited interferon (IFN)-γ (Th1) and IL-17 (Th17)–producing cells. At clinical therapeutic concentrations, SRL, however, significantly increased forkhead/winged helix transcription factor P3 (FOXP3+) Tregs, whereas TAC inhibited this T-cell population dose dependently and significantly. When used in combination, TAC and SRL had additive effects on inhibition of IFN-γ– and IL-17–producing cells. This was in contrast to the ability of SRL to reverse TAC-mediated inhibition of FOXP3-expressing cells. Proinflammatory cytokines (IL-1β, IL-6, and tumor necrosis factor-α) added to cultures caused significant decrease in FOXP3+ Tregs that was again reversed by SRL. Sirolimus-derived Tregs were phenotypically normal, anergic to allostimulation, and suppressed proliferation of allogeneic effector T-cells. Conclusions Thus, although TAC inhibits all alloreactive T cells, SRL promotes the differentiation and expansion of donor-specific Tregs without secondary reprogramming to IFN-γ+FOXP3+ and IL-17+FOXP3+ Treg subsets. These results, although performed in an artificial in vitro model, add clinically applicable information on how these agents affect T-cell subpopulations.